Integrated Smart Gate for Vehicles and Pedestrian - Vaibhav Londhe; Tushar Ladhane; Harshad Dhavle; Dr. Sudhir Divekar (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Traditional authentication methods like manual verification or keycard access are often cumbersome and prone to errors. To address these challenges, a Smart Gate for Vehicles and Pedestrians Using Face Detection has emerged as a viable solution that uses advanced technologies for seamless access control. This system integrates face detection technology with automatic gates for both vehicles and pedestrians, ensuring efficient and secure entry and exit to restricted areas. Face detection is a reliable and nonintrusive method for identification, eliminating the need for physical tokens or credentials. The system enhances convenience and security by automating the verification process. The integration of machine learning algorithms allows for continuous improvement in accuracy. This paper discusses the design, implementation, and potential impact of a Smart Gate System powered by face detection.
Keywords: Smart Gate; Face Detection; Access Control; Security; Automation